How Does Mental Accounting Influence Financial Decision-Making Among New Employees in Indonesia? - Rifani, Riza Amalia; Adriansyah, Adriansyah; Iqra, Muhammad Nur Farid (Amsir Accounting & Finance Journal, 2025)
Mental accounting is a concept that explains how individuals categorize, group, and evaluate their economic decisions. The study hypothesizes that income and expense categorization, as well as allocation preferences, influence the financial decision-making of new employees. The research uses a quantitative approach with a descriptive method, collecting primary data through a questionnaire distributed to 200 new employees in Indonesia. The results show that both income and expense categorization and allocation preferences significantly influence the financial decision-making of new employees.